HIV and me: The perceptions of children aged 10–12 living with HIV, and their expectations for adulthood - Hettie Van der Merwe; Alva Van der Merwe (Koers : Bulletin for Christian Scholarship, 2020)
This article explores the understanding that children living with HIV have of their condition, and the physical and psychosocial challenges they face in pursuit of their ideals for adulthood. Analysis of the interview data, preceded by drawing-and-telling, confirmed literature findings on the importance of communication for complete disclosure and the need for repetitive discussions about HIV-related burdens to supplement medicine and treatment in pursuit of holistic well-being for children living with HIV. Research findings revealed children’s limited cognition of their HIV condition and their challenges with physical pain (attributable to their medicines and treatment) and psychosocial pain (stemming from family fragmentation and stigma). The children exhibited an intense desire for respect for their existence and for the realisation of their right to participate actively in communication regarding their HIV status. Their ideals for adult life pertained to being of benefit to others. The findings contribute to the discourse on effecting holistic wellbeing for children living with HIV.